Development of an Information Sharing Methodology in Project Management - Vávra, Jan; Pauknerová, Daniela, 1970-; Perez Burdalo, Margot; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The Master’s Thesis develops an updated information sharing methodology to improve communication between the Project Management Office (PMO) and the Project Managers during a complex organizational transition period following a spin-off. The primary research question examines the specific steps the PMO can take to effectively communicate information to the Project Managers. Secondary questions aim to identify the shortcomings of the current methodology, tailoring industry best practices to the context of the organization, and implementation of insights from the project managers toward updating the methodology. The updated methodology is based on the combination of a theoretical framework, laying the groundwork and establishing industry best practices, and a practical analysis gathering insights from the project managers to assess the current methodology. The theoretical framework consist of the topics of knowledge transfer, change management, stakeholder feedback, and methodology for qualitative interviews. Practical analysis covers semi-structured qualitative interviews with 9 project managers in the technological department. The recommendations of the Master’ thesis can be directly applied to the context of the organization, along with developing the new methodology, the author of the thesis proposes also recommendations for future research to ensure longevity of the methodology.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses